Review of Afrotropical Glenosema Kieffer (Hymenoptera, Bethylidae) with description of 13 new species - Azevedo, Celso O.; van Noort, Simon (Zootaxa, 2019)
The Afrotropical species of Glenosema are reviewed. Seventeen species are recognized, four previously described species, G. niloticum (Kieffer), G. durum Barbosa, Kawada & Azevedo, G. denteatum Lanes & Azevedo and G. elevatum Lanes & Azevedo, and thirteen species described and illustrated as new: G. qaqambile sp. nov., G. deki sp. nov., G. ebazileyo sp. nov., G. tyaba sp. nov., G. umphanda sp. nov., G. banzi sp. nov., G. bubanzi sp. nov., G. ahlukileyo sp. nov., G. icephe sp. nov., G. mxinwa sp. nov., G. lingana sp. nov., G. uphahla sp. nov. and G. tyheli sp. nov. A key to the Afrotropical species is presented. We highlight potential character suites that may be phylogenetically significant and consider evolutionary scenarios that may have led to the present distribution pattern associated with semi-arid areas on the African continent.